An Insight to Burn Related Maternal Morbidity and Mortality in Pregnancy - Rijal, H; Rana, A; Chalise, G (Nepal Journal of Obstetrics and Gynaecology, 2015)
Aims: The aim of this study is to study morbidity and mortality of burn cases during pregnancy and postpartum period. Methods: This is a retrospective study conducted at Tribhuvan University Teaching Hospital from April 1998 to July 2014. The data were retrieved from the records in burn ward, intensive care unit and emergency unit. Pregnant women with burn were studied for the nature, degree and the percentage of burn in relation to pregnancy outcome and mortality. Results: There were 32 cases of burn patients with pregnancy. The most common source of burn was kerosene-induced flame (23) followed by domestic firewood (7), boiling water (1) and lightening (1).There were 25 cases of accidental burn and seven were suicidal burn. The age of the patients was ?19 years in 7, 20-24 in 13, 25-29 in 6 and 30-34 in 6 patients. Except for two cases of postpartum burn , all the others occurred during pregnancy between 6-40 gestational week<12weeks =5, 13-27 weeks =10, 28-36 weeks=4, 37-42 weeks =6 and unknown =7. There was only one cesarean and three vaginal births and most resulting in stillbirth owing to higher percentage of burn above second degrees. The percentage of burn was <30% in 13, 30- 39% in 3, 40-59 % in 6, 60-69% in 5 and 70-90% in 2 patients. There were nine mortality (28.1%) in women above 30% burn. Conclusions: The most common cause of burn in pregnancy was flame burn. Pregnant women need to be cautioned against flame burn and avoid using kerosene cooking stove to prevent themselves from burn, genuinely necessary steps to be propagated by all healthcare providers and also at the same time counseling against suicide to be done.